2018
DOI: 10.11616/asbed.v18i38800.459462
|View full text |Cite
|
Sign up to set email alerts
|

Yöneti̇ci̇m Eti̇k Bi̇r Li̇der Mi̇di̇r?: Beyaz Yaka Çalişanlarin Algisi Üzeri̇ne Bi̇r Çalişma

Abstract: Öz Birey, grup, işletme ya da toplum, analiz birimi ne olursa olsun, sosyal bilimlerde etik her zaman araştırılan bir konu olmuştur. Konunun cazibesi, kavramın yerleşik ama bir o kadar da muğlak, göreceli ve tartışmaya açık olmasından kaynaklanmaktadır. Bu ikilik, kavramın kendisinin ve iş etiği, işyerinde etik kodlar, etik liderlik gibi türevlerinin ölçümündeki zorlukları da beraberinde getirmektedir. Bir yöneticinin etik davranışlarının toplamı anlamına gelen etik liderlik, akademisyenlerce yöneticiler için … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In Zincir & Tunç's (2018) study, ethical leadership is discussed in terms of its dimensions: human orientation, sustainability and ethical guidance, role clarity, and honesty. The research on 175 whitecollar employees revealed that employees perceive whether their managers are ethical.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zincir & Tunç's (2018) study, ethical leadership is discussed in terms of its dimensions: human orientation, sustainability and ethical guidance, role clarity, and honesty. The research on 175 whitecollar employees revealed that employees perceive whether their managers are ethical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be speculated that the leader's mentorship aspect, not only ethical, has yet to mature. (Zincir & Tunç, 2018). In Brown et al (2005), the perception of ethical leadership is that ethical leaders measure success not only by results but also by their methods, make fair decisions, are reliable, and act by prioritizing the interests of employees.…”
Section: Literature Reviewmentioning
confidence: 99%